Heteropoly Acid Catalyzed Micheal Addition of Benzene Sulfonamide to Ethyl Acrylate - Wang, Desheng; Yan, Liang; Wang, Xiaolai (Asian Journal of Chemistry, 2012)
The solvent-free aza-Michael addition reaction of benzene sulfonamide to ethyl acrylate carried out in presence of catalytic amount of different. Keggin type heteropoly acids as reusable catalyst in solvent-free condition has been investigated. Pure N-alkylsulfonamide was obtained and the structure of N-alkylsulfonamide was identified by GC-MS, FT-IR and 1H NMR spectra. It is found that H3PW12 had the best activity affording N-alkylsulfonamide with excellent yield of 93 %. The effects of experimental factors on the catalytic aza-Michael addition reaction and the catalytic recycling of H3PW12 catalyst were studied. H3PW12 catalyst exhibited good catalytic activity after 5 times of running. The undemanding catalytic separation and the reusability of the H3PW12 catalyst is hopefully to be beneficial to the exploration of green chemistry and environmental benign procedure for the synthesis of N-alkylsulfonamide.